Factors Associated with the Incidence of Anemia in Pregnant Women at Risk of Stunting in Batanghari Regency - Ismi Nurwaqiah Ibnu; Silvia Mawarti Perdana; Kasyani Kasyani (Journal of Global Nutrition, 2025)
The nutritional status of pregnant women is a factor that can influence stunting in toddlers as seen from the status of upper arm circumference measurements in the 3 month period of pregnancy. Based on the results of the 2021 Indonesian nutritional status survey, stunting in Batanghari Regency decreased to 24%, and in the 2022 Indonesian nutritional status survey, stunting in Batanghari Regency increased to 26%. Therefore, pregnancy is a critical period, which can affect the continuity of life in the future. Research Method: quantitative research through analytical observational with a cross sectional design. This research was conducted in the Community Health Center Work Area in Batanghari Regency, which is based on the highest prevalence of stunting in toddlers in 2022 in Batanghari Regency. The duration of the research was approximately 8 (eight) months from March to November 2023. The number of samples in this study was 245 pregnant women. The inclusion criteria in this study were pregnant women in the second trimester and third trimester. Research results show that the prevalence of anemic pregnant women in Batanghari Regency is 40.4%. Factors that influence pregnant women with anemia which are statistically significant are family income, upper arm circumference of pregnant women, body mass index of pregnant women, TT injection services, blood pressure check services. , services for administering blood supplement tablets, uterine fundus height services. Suggestion: increase access to health services for pregnant women, so that pregnant women will be exposed to information about the impact of anemia and improving nutritional and health status in other aspects can influence the anemia status of pregnant women